Peripartum management of diabetes - Pramila Kalra; Manjunath Anakal (Indian Journal of Endocrinology and Metabolism, 2013)
The peripartum control of diabetes is very important for the well-being of the newborn as higher incidence of neonatal hypoglycemia is seen if maternal hyperglycemia happens during this period. Type of diabetes (type 1, type 2 or gestational diabetes) also has an effect on the glucose concentration during intrapartum period. During the latent phase of labor, the metabolic demands are stable but during active labor there is increased metabolic demand and decreased insulin requirement. After delivery once the placenta is extracted, insulin resistance rapidly comes down and in patients with pre-gestational diabetes there will be a sudden drop in insulin requirement and the insulin may not be required in women with gestational diabetes, but they just need close monitoring. During breast-feeding blood glucose levels fall because of high metabolic demand and women need to take extra calories to maintain the levels and more vigilance especially in type 1 and type 2 diabetic mothers is required. The protocols used for the management of peripartum management of diabetes mostly rely on glucose and insulin infusion to maintain maternal blood sugars between 70 and 110 mg/dl. The data is mostly from retrospective studies and few randomized control trials done mainly in type 1 diabetes patients. The review summarizes guidelines, which are used for peripartum management of blood glucose.